Efficient elimination of highly lethal Vibrio parahaemolyticus in shrimp aquaculture by a vibriophage - Mingrui Li; Huaijin Jiang; Keming Shi; Haoyu Huang; Xiaojun Wang; Fang Li; Ke Pan; Yunlan Yang; Rui Zhang (Fish & Shellfish Immunology, 2026)

Distinct ecophysiological characteristics of two genetically similar vibriophages - Wenqing Li; Runqi Zhu; Keming Shi; Huiyu Ding; Shiying Ren; Song Xu; Jing Zhao; Nianzhi Jiao; Yunlan Yang; Rui Zhang (Marine Life Science & Technology, 2026)

A broad-spectrum vibriophage with potential for phage therapy against Vibrio alginolyticus in shrimp aquaculture - Keming Shi; Huiyu Ding; Wanxuan Zhong; Wenqing Li; Min Hsiao; Bu Xu; Haipeng Guo; Jing Zhao; Jie Xu; Demin Zhang; Yunlan Yang; Rui Zhang (Aquaculture, 2026)

A lytic vibriophage as a potential biocontrol agent against vibriosis in aquaculture - Yunlan Yang; Wanxuan Zhong; Huiyu Ding; Keming Shi; Haipeng Guo; Demin Zhang; Lanlan Cai; Min Hsiao; Jie Xu; Rui Zhang (Fish & Shellfish Immunology, 2025)

Integrating larval zebrafish model and network pharmacology for screening and identification of edible herbs with therapeutic potential for MAFLD: A promising drug Smilax glabra Roxb. - Yinjuan Xiong; Xixuan Huang; Yuxin Li; Yukang Nie; Haodong Yu; Yaqi Shi; Jiajie Xue; Zhehui Ji; Keming Rong; Xuezhen Zhang (Food Chemistry, 2025)

A study of the pharmacokinetics of clozapine and its metabolites by the dynamics of its distribution in the oral fluid of healthy volunteers - Qianwen Shi; Lele Wang; Qian Zheng; Yefei Pan; Xiaohui Tan; Yao Liu; Shanlin Fu; Ande Ma; Zhiwen Wei; Keming Yun (Archives of Toxicology, 2024)

A comprehensive review of research on indoor cognitive performance using electroencephalogram technology - Nan Zhang; Chao Liu; Jiaxin Li; Keming Hou; Jing Shi; Weijun Gao (Building and Environment, 2024)

Contrasting currents drive geographic variability in the biomass of Pacific saury (Cololabis saira), zooplankton, and phytoplankton in the northwestern Pacific - Yuqiu Wei; Zhengguo Cui; Yongqiang Shi; Xiujuan Shan; Bingzhang Chen; Keming Qu; Quandong Xin; Tao Jiang; Jufa Chen (Progress in Oceanography, 2023)

Prediction of Longwall Progressive Subsidence Basin Using the Gompertz Time Function - Jian Wang; Keming Yang; Xiangping Wei; Xiaoyu Shi; Shuyi Yao (Rock Mechanics and Rock Engineering, 2022)

Mussel Byssal Attachment Weakened by Anthropogenic Noise - Xinguo Zhao; Shuge Sun; Wei Shi; Xuemei Sun; Yan Zhang; Lin Zhu; Qi Sui; Bin Xia; Keming Qu; Bijuan Chen; Guangxu Liu (Frontiers in Marine Science, 2021)
The increasing underwater noise generated by anthropogenic activities has been widely recognized as a significant and pervasive pollution in the marine environment. Marine mussels are a family of sessile bivalves that attach to solid surfaces via the byssal threads. They are widely distributed along worldwide coastal areas and are of great ecological and socio-economic importance. Studies found that anthropogenic noise negatively affected many biological processes and/or functions of marine organisms. However, to date, the potential impacts of anthropogenic noise on mussel byssal attachment remain unknown. Here, the thick shell mussels Mytilus coruscus were exposed to an ambient underwater condition (∼50 dB re 1 μPa) or the playbacks of pile-driving noise (∼70 or ∼100 dB re 1 μPa) for 10 days. Results showed that the noise significantly reduced the secretion of byssal threads (e.g., diameter and volume) and weakened their mechanical performances (e.g., strength, extensibility, breaking stress, toughness and failure location), leading to a 16.95–44.50% decrease in mussel byssal attachment strength. The noise also significantly down-regulated the genes expressions of seven structural proteins (e.g., mfp-1, mfp-2, mfp-3, mfp-6, preCOL-P, preCOL-NG, and preCOL-D) of byssal threads, probably mediating the weakened byssal attachment. Given the essential functions of strong byssal attachment, the findings demonstrate that the increasing underwater anthropogenic noise are posing a great threat to mussel population, mussel-bed community and mussel aquaculture industry. We thus suggest that future work is required to deepen our understanding of the impacts of anthropogenic noise on marine invertebrates, especially these with limited locomotion ability, like bivalves.

Vascular plant species richness on wetland remnants is determined by both area and habitat heterogeneity - Jianmin Shi; Keming Ma; Jifeng Wang; Jingzhu Zhao; Kate He (Biodiversity and Conservation, 2010)